Evaluation of optimal analysis, design, and testing of electromagnetic shunt damper for vibration control of a civil structure. Issue 3 (21st December 2019) - Ao, Wai Kei; Reynolds, Paul
Summary: The current study is to find out alternative damping to provide satisfactory vibration suppression performance in civil engineering. Accordingly, electromagnetic actuators and electromagnetic dampers (EMDs) are utilised to generate electromagnetic damping. For further discussion on control of vibration serviceability problem in civil structure, the use of a linear voice coil motor (LVCM) as an EMD is implemented to attenuate unwanted vibration. To induce appropriate electromagnetic damping, the terminal ends of the LVCM need to connect with shunt circuits. The basic resistor series circuit and resistor, inductor, and capacitor (RLC) oscillating circuit are employed to connect to the LVCM in terms of enhancing the EMD damping. However, a design of the electromagnetic shunt damper (EMSD) is required with the generic H ∞ and H 2 robust optimisation techniques to determine shunt circuit components, in which the results of these optimisations were discussed on the previous author study. For extending the EMSD study, the resulting EMSD is experimentally exploited to a six‐storey aluminium frame structure. The random and harmonic excitations are selected to input to the structure to examine the performance of the electromagnetic damping. The finding of the experimental test of the EMSD gives satisfactory vibration suppression performance.